PENGARUH RELIGIOSITAS, PERILAKU TIDAK ETIS, DAN KEEFEKTIFAN PENGENDALIAN INTERNAL TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (STUDI EMPIRIS PADA BANK UMUM SYARIAH DI KOTA BANDA ACEH) - Maulidya, Zuhra; Fitri, Yulia (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
The purpose of this research is to examine the influence of religiosity, unethical behavior, and effectiveness of internal control to tendency of accounting fraud (Empirical Study on Islamic Bank in the city of Banda Aceh). The population of this study were the managers and internal auditors of Islamic bank with the total 33 respondents. The research was conducted by using census method. The data source in this study are primary data obtained from questionnaires to the respondent. The testing of the influences of independent variables toward dependent variables was done by using multiple linear regressions model. The results of this research showed that both partially and simultaneously, religiosity, unethical behavior, and effectiveness of internal control were significantly influential tothe accounting fraud on Islamic bank in the city of Banda Aceh.